Landslide Morphology and Mobility on Ceres Controlled by Topography. Issue 12 (19th December 2020) - Johnson, Brandon C.; Sori, Michael M.
Abstract: Ceres has an abundance of long runout landslides with more slides near the poles. Here we simulate these landslides using a discrete element model. Our simulations indicate that long runout landslides on Ceres do not require the presence of fluid or slippery ice to explain their mobility. We find that lower fall heights and larger volumes lead to increased slide mobility while the relatively low surface gravity of Ceres, compared to the Earth and Mars, reduces slide mobility and affects slide morphology. We show that latitudinal trends in number of slides and slide morphology are more consistent with trends in topography than expected trends in near‐surface ice content. These morphological trends with topography are also consistent with the results of our landslide simulations. We argue that landslide morphology cannot be used to draw conclusions about local ice content and composition. However, the higher abundance of long runout landslides on Ceres relative to Vesta may be related to its higher global ice content or greater endogenic activity. Plain Language Summary: Ceres has many large landslides that are longer than expected indicating a high mobility. Many of these landslides are located near the poles of Ceres, and landslides near the poles have a different appearance to those near the equator. We simulate the formation of these landslides using a computer code and reproduce the high mobility of these slides without including lubrication, which would tend to increase mobility. Our simulations show slides that fall from large heights look similar to landslides near Ceres poles and tend to be less mobile than those originating from smaller heights. We find that the greater number of craters and more rugged topography near the poles of Ceres likely explains the large number of landslides near the poles and variations in landslide appearance with distance from the equator. The appearance and abundance of landslides likely does not tell us about the composition and ice content near the Cerean surface. Key Points: Using a discrete element model, we simulate landslides on Ceres reproducing mobility trends and slide morphologies The presence of more Type 1 landslides at high latitudes is best explained by variations in crater density and topography with latitude Cerean landslides do not currently provide robust information regarding ice content and composition of the subsurface